ISO27001/ISO27002 : Ein Taschenführer - Calder, Alan (IT Governance Publishing, 2017)
Information is one of your organization's most important assets, and keeping it secure is vital to your business. This handy pocket guide provides a basic overview of the two main information security standards, with the formal requirements (ISO27001:2013) for creating an Information Security Management System (ISMS) and best practice recommendations (ISO27002:2013) for anyone wanting to adopt, implement or have to manage.An ISMS based on the ISO27001/ISO27002 standard offers numerous advantages:Improve your efficiency with information security systems and practices that allow you to focus on your core business Protect your information assets from a range of cyber threats, criminal activities, insider compromises and system failures Systematically manage your risks and create plans to eliminate or mitigate Cyber ​​ThreatsDetect and Remediate Threats or Process Errors SoonerThe Next Step to Certification?You can have an independent audit of your ISMS against the specifications of the ISO27001 standard and, if this confirms the compliance of your ISMS, you may receive an accredited certification. We publish a number of ISMS-related toolkits and books (like "Nine Steps to Success") to help you along the way.ContentsThe ISO/IEC 27000 family of information security standards;Background of the standards;Difference specification - Guidance;Certification process;The ISMS and ISO27001;Overview of ISO/IEC 27001:2013;Overview of ISO/IEC 27002:2013;Documents and records;Management responsibility;Process approach and PDCA Cycle; Context, Policy and Scope; Risk Assessment; The Statement of Applicability; Implementation; Review and Action; Management Review; ISO27001 Annex A; About the AuthorAlan Calder is Founder and Chief Executive Officer of IT Governance Ltd, an information, analytics and consulting firm that helps organizations manage IT governance, risk management, compliance and information security issues. He has many years of experience in senior management in the private and public sector.This handy pocket guide provides a basic overview of the two most important information security standards - buy it today and learn how to protect your organization's most valuable asset.